Possibilities and Challenges of Radio Frequency Energy Harvesting in Dar es Salaam, Tanzania - Isingo, Fredrick; Mafole, Prosper; Abdalla, Abdi (Tanzania Journal of Engineering and Technology, 2021)
This paper presents investigation on the possibilities and challenges of harvesting ambient Radio Frequency Energy (RFE) at Dar es Salaam region in Tanzania. The Radio Frequency (RF) signals were measured using a Rohde and Schwarz FSC 3 spectrum analyzer observing available frequencies with their respective power. Among several RF signals received, the most powerful signals observed were; 800 MHz, 950 MHz, 2100 MHz and 2400 MHz, having average signal strengths of about -30.29 dBm, -35.94 dBm, -42.90 dBm and -30.42 dBm respectively. The power possessed within these frequencies were suitable to be harvested due to their signal strengths, an overall power average of -34.89dBm was obtained and a multi narrowband harvester was designed and simulated using real-time values on Keysight ' s Advanced Design System (ADS) 2019. The simulation results confirm a promising possibility of harvesting RF energy to power ultra-low-power devices in the Internet of Things (IoT) and beyond. Key words: DC-DC Boost, Energy Harvesting, Impedance matching, RF-DC conversion Schottky Diode, Super Capacitor array, Voltage multipliers.